STUDY OF REACTION TEMPERATURE EFFECTS ON THE YIELD AND QUALITY OF BIODIESEL SYNTHESIS FROM WASTE PALM OIL - Roza, Faizatin Nadya; Widyaningrum, Sri Rahayu; Alvita, Livia Rhea; Rezki, Amelia Sri (Indonesian Journal of Pure and Applied Chemistry, 2025)
Biodiesel is one of the alternative renewable energy resources to petroleum diesel. It has gained significant attention due to its biodegradability, lower emissions, and compatibility with existing diesel engines. Usually, producing biodiesel requires a reaction called transesterification. It is the most popular way to turn oils into biodiesel. It basically involves mixing triglycerides with alcohol and a catalyst. Reaction temperature is one of the most important factors that impact the transesterification process. The research investigated how the different reaction temperatures could affect biodiesel's quality and physicochemical results synthesized from waste palm oil. The subject of the research was temperature treatment divided into five groups, which were 50 °C, 55 °C, 60 °C, 65 °C, and 70 °C. A quantitative method was implemented to analyze biodiesel quality from waste palm oil. The quantitative data from biodiesel production were the yield and its byproduct, as well as the percentage level of the free fatty acid (FFA) as a result of physicochemical analysis of biodiesel. The result of the research was that the optimum temperatures to produce biodiesel synthetically were 55 °C and 60 °C because both had the highest biodiesel yield percentage and glycerin volume compared to other reaction temperature treatments. Additionally, all the reaction temperature treatments resulted in FFA levels under 0.5% for biodiesel products. They experienced a decline in raw material, waste palm oil, which had more than 0.75% until ~1% of FFA levels for each reaction temperature. The biodiesel's FFA levels showed that the study's biodiesel met international production standards.